Socioeconomic Factors Associated with Readmission after Deceased Donor Renal Transplantation. Issue 7 (July 2017) - Whitlock, Richard S.; Seals, Samantha; Seawright, Ashley; Wynn, James J.; Anderson, Christopher; Earl, Truman M.
Early hospital readmissions after kidney transplantation pose a significant financial burden and hardship for patients and health-care institutions alike. We sought to identify the risk factors associated with increased likelihood of readmission after transplantation, and examined to determine whether patient socioeconomic demographics impacted the likelihood of perioperative readmissions. We evaluated all deceased donor renal transplants performed at our institution between August 2011 and December 2015. In a cohort of 325 transplant operations that met our inclusion criteria, 117 (36%) were readmitted to the hospital within 90 days of discharge. In univariable analyses, length of stay and pretransplant disabled status were associated with increased likelihood of readmission within 90 days of transplant. When placed into multivariable models, there was a suggestion association with length of stay and disability status. Kidney donor profile index, estimated posttransplant survival, employment, race, age, and payor status were not associated with readmission. In conclusion, the factors associated with posttransplant readmission are not necessarily influenced by socioeconomic factors in our study population. The data collected in this single center study indicate that the factors associated with increased rates of readmission are likely clinical in nature.